Assessment Of Serum Testosterone Levels In Men With Controlled And Poorly Controlled Type 2 Diabetes Mellitus In Erbil City (The Review of Diabetic Studies, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a common condition marked by insulin resistance and high blood sugar. It can cause many health problems, including hormone issues, nerve damage, kidney disease, and heart problems. One of the less recognized complications is low testosterone, which can affect quality of life and increase the risk of heart disease. Methodology: This study is a cross-sectional survey carried out at Bahirka Hospital and the Diabetic Center in Erbil, Kurdistan, between April 2024 and June 2025. Information was collected using a structured questionnaire, and blood tests were done to measure testosterone levels. A small pilot study with 5 patients was first done to check feasibility, but those cases were excluded from the final results. The study included 100 men aged 40–70 years with type 2 diabetes for more than one year. Patients with other conditions or treatments that could affect testosterone were excluded. In the final analysis, 50 men had poorly controlled diabetes and 50 had controlled diabetes. Results: The mean age of controlled type 2 diabetic patients was 57.4 ± 1.2 years, slightly higher than poorly controlled patients at 54.8 ± 1.1 years. Mean BMI was also higher in poorly controlled patients (33.2 ± 0.8) compared to controlled cases (29.1 ± 0.7). Overall, 80% of participants were overweight or obese, with 46% overweight, 34% obese, and only 20% having normal BMI. Poorly controlled patients had significantly more cases of severely low (10%) and low testosterone (34%) compared to the controlled group. Normal testosterone was more frequent in controlled cases (60% vs. 36%), as were borderline levels (34% vs. 20%). A significant association was found between low testosterone and poor glycemic control (P < 0.05). Conclusion: This study found a significant link between poor glycemic control and reduced testosterone levels in men with type 2 diabetes, with poorly controlled patients showing lower testosterone, higher BMI, and slightly younger age.